Student Self-Directed Learning Strategies In Improving English Speaking Skills In Senior High Schools - Rifka, Rifka; Suryanto, Bradhiansyah Tri (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
This research investigates the self-directed learning (SDL) strategies employed by senior high school students to improve their English speaking skills. Using a qualitative narrative inquiry approach, the study explores students’ personal experiences in planning, implementing, and evaluating their independent learning activities. Data were collected through interviews, observations, and document analysis, focusing on how learners manage their study routines, select learning resources, and overcome speaking challenges. The findings reveal that students adopt a combination of cognitive, metacognitive, and socio-affective strategies, such as shadowing native speakers, self-recording, engaging in peer conversations, and utilizing digital applications. Intrinsic motivation, discipline, and self-confidence emerge as crucial internal factors, while access to resources, supportive environments, and technology serve as external enablers. The study concludes that SDL enhances students’ fluency, accuracy, and confidence in speaking English, particularly when strategies are aligned with learners’ preferences and supported by conducive learning conditions.